DIGITAL SYSTEM BLOCKCHAIN SEBAGAI STRATEGI UNTUK OPTIMALISASI PENGELOLAAN DANA ZAKAT: STUDI KONSEPTUAL - Urfiyya, Khalida; Sulastiningsih, Sulastiningsih (Jurnal Studi Agama dan Masyarakat, 2021)
Digitalization is a new phenomenon in the early twenty-first century connecting technology with civilization and benefits mankind in an intelligent and efficient way. The adoption of the blockchain concept in zakat institutions is the time to be a solution in dealing with existing Islamic problems such as the collection and distribution of zakat funds. This study was to provide an overview of the opportunities, potential and capabilities of blockchain system adoption in zakat institutions, especially in Indonesia. The method was a literature study by reviewing various relevant literatures and balanced with related studies on phenomena in various countries. With dynamic technological developments, especially the emergence of blockchain technology, the zakat ecosystem can be further enhanced since blockchain offerred the concept of data decentralization which were permanent, real-time, secure and transparent. Several things to encourage this practice could be done